Interdependence in shared goal pursuit among established and impromptu dyads: Expectations, allocation, and performance - vanDellen, Michelle R.; Wright, Julian W. C.; Finkel, Eli J.; Fitzsimons, Grainne M.; Hall, Andrew (Frontiers in Social Psychology, 2025)
IntroductionTransactive goal dynamics theory asserts that interdependent partners have opportunities and motivation to learn about each other's idiosyncratic skills and interests in goal pursuit, producing enhanced system-level knowledge and performance. These shared knowledge structures of each other's skills and preferences should produce more efficient allocation of tasks to complete in goal pursuit. The present study directly tests this hypothesis using an empirical demonstration that allows for a comparison of shared goal pursuit among couples with experimentally manipulated interdependence. Specifically, we examined how people allocated and subsequently completed individual tasks toward a shared outcome when working with an established partner compared to working with an impromptu gender-matched partner.MethodTo accomplish these aims, we recruited two pairs of romantic partners to complete a laboratory session. Each couple was randomly assigned to complete a series of tasks as part of either an established dyad (i.e., couples worked together) or impromptu dyad (i.e., couples traded partners).ResultsEstablished dyads (a) considered the system's strengths in dividing tasks and (b) divided tasks more effectively than impromptu dyads. Established dyads also expected to and did perform better than impromptu dyads.DiscussionThese findings characterize how goal interdependence manifests in close relationships.